Treatment for Gulf War Illness (GWI) with KPAX002 (methylphenidate hydrochloride + GWI nutrient formula) in subjects meeting the Kansas case definition: A prospective, open-label trial - Holodniy, Mark; Kaiser, Jon D. (Journal of psychiatric research, 2019)
This study tested the safety, tolerability, and efficacy of KPAX002—a combination of methylphenidate hydrochloride plus a micronutrient formula designed to support mitochondrial function—as a treatment for Gulf War Illness (GWI). This open-label trial enrolled 17 subjects meeting the Kansas case definition for GWI. Of the 17 subjects enrolled, 15 qualified for the Intent-to-Treat (ITT) population with 10 subjects completing the trial per protocol. All analyses were on the ITT population. At 12 weeks, subjects taking KPAX002 experienced a mean 25% reduction in their overall GWI symptoms severity as measured by the GWI Symptoms Assessment Tool (SAT) (p < 0.001). Visual analog scale scores were also significantly reduced for fatigue (p = 0.019), cognitive symptoms (p = 0.006), sleep problems (p = 0.026), and pain (p = 0.05). Twelve weeks of KPAX002 administration resulted in a significant improvement in GWI symptoms with an acceptable side effect profile. A larger randomized, double-blinded, placebo-controlled trial is necessary to determine if the observed benefit can be replicated.